A feasibility (pilot) mixed methods study of an innovative non-pharmacological breath-based yoga and social-emotional intervention program in an at-risk youth sample in London, Canada - Akshya Vasudev; Emily Ionson; Janani Sathiaselan; Anurag Thatipalli; Aman Chauhan; Christine Hassan; Javeed Sukhera; Mark Speechley; Cheryl Forchuk (Pilot and Feasibility Studies, 2024)
Abstract Background Various service provision models for youth at risk of homelessness have been researched and implemented, including access to housing and physical and mental health resources. However, even with these interventions, we remain unaware of how best to manage symptoms of depression and anxiety and the rate of drug use in these populations primarily because of a lack of feasibility data. Methods This paper presents the results of a mixed-methods study in London, Canada, that examined the feasibility of implementing a biopsychosocial intervention, SKY Schools, in at-risk youth aged between 16 and 25 (n = 49). The study also recorded qualitative responses about the program’s usefulness from the perspective of the service users. The SKY Schools intervention consisted of social-emotional learning combined with Sudarshan Kriya Yoga, a standardized yoga-based breathing exercise routine. The intervention program was divided into two phases: an active learning phase and a reinforcement phase. The following feasibility outcome measures were collected: (1) the number of potential participants approached per month, (2) number (proportion) who were successfully screened, (3) the proportion of screened participants who enrolled, (4) the rate of retention in the study, (5) rate of adherence to study protocol, (6) proportion of planned ratings that were completed, (7) intervention cost per case, (8) completeness of final data for analysis, (9) length of time to collect all data, (10) quality of all collected data, (11) determining if partnering community organizations were willing to conduct the study as per study protocol, (12) determining if there were any capacity issues with partners providing intervention and investigators being able to perform the tasks that they were committed to doing, (13) determining if there were any problems of entering the data into a computer, (14) preliminary data about the safety of the intervention, and (15) preliminary estimate of treatment effects. Results All feasibility outcome measures were collectible. In the city of London, Canada it was feasible to conduct a pilot study in this population of youth at risk of homelessness. Foremost among the findings was a high retention rate (61.2%) and overall positive qualitative feedback with a number of potential suggestions to improve the delivery and quality of the intervention. However, we had a significantly low recruitment rate (0.27 participants per week) suggesting that multiple sites will be needed to achieve an adequate sample size for a subsequent definitive trial. Conclusions Future researchers may consider the findings of this feasibility study when designing a randomized control trial to further assess the efficacy and tolerability of SKY Schools. Trial registration Trial registration: Clinicaltrials.gov, identifier NCT02749240. Registered April 22, 2016, https://clinicaltrials.gov/ct2/show/NCT02749240 .